A review of gender integration in African food-system policies: insights from Nigeria, Tanzania, Egypt and Kenya - Frimpong-Wiafe, Belinda; Muchiri, Caroline; Mawia, Harriet; Enahoro, Dolapo K. (2025)
Ensuring gender equality is a crucial aspect of achieving development goals, particularly in low- and middle-income countries (LMICs). Policymaking stands as a key avenue through which governments can actively pursue gender-responsive development. In LMICs—where agriculture often plays a pivotal role in the economy, and rural livelihoods are closely tied to food value chains—the integration of gender in agricultural and food-system policies is paramount. This is particularly true for many African countries. Although many African governments have recognized the importance of gender equality in agricultural and related sectors, gender disparities still persist in these sectors. This study evaluates national policies across various sectors in Nigeria, Tanzania, Egypt and Kenya, considering gender-based distinctions in the needs and priorities of women and men. Employing tools adapted to the broader context of food systems, the analysis of 54 sectoral policy documents reveals an encouraging pattern at first glance—that 89.9 percent of documents integrate gender considerations and perspectives. However, we identify specific gaps in the integration of gender considerations in national policies related to food systems, such as agriculture, livestock, and climate change. This could differentially affect how women and men derive benefits from ongoing or future changes in the countries’ food systems.